THE EXCHANGE SPHERE IN THE SOLIDARY ECONOMY: SOLIDARY COMMERCE AND CONSUMPTION IN THE CITY - de Godoy, Tatiane Marina Pinto (Revista Cidades, 2021)
Exchange is a condition for the reproduction. Production and consumption, mediated by distribution and by exchange, are inseparable spheres as states Karl Marx in Introduction to the Political Economy Critic (2008). Identifying and analyzing the exchange forms in the Solidary Economy and its relation with the space produced by capitalism brings to us a new understanding possibility about the social reproduction conditions. The objective of the text is to develop a critical analysis of the conditions of the exchange forms reproduction of the Solidary Economy, especially of the commerce and solidary consumption.